Metal and non-metallic element co-doped oxyhalide solid electrolyte and all-solid-state battery
By mixing metal and non -metallic elements in halide solid electrolytes, its ion conductivity has been improved, the existing halide solid electrolyte conductivity is low, and battery applications with high safety performance and high energy density are realized.
Patent Information
- Application Number
- CN202411474810.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The ionic conductivity of existing halide solid electrolytes is generally low, limiting their performance in battery applications.
Moisturizing metal elements such as CS, NB, HF, LA, Y, Fe, GA, IN, PB, BI, GE, SB, etc. and non -metallic elements such as S, SE, TE, O, etc. Non -metallic elements are doped with halide solid electrolytes to improve their ionic conductivity.
It significantly improves the ion conductivity of the halide oxide solid electrolyte, and partly reaches 10 × 10-3S CM-1, which improves the safety performance and energy density of the battery.
Smart Images

Figure CN119381525A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage batteries, and more specifically, to a halogen oxide solid electrolyte co-doped with metal and non-metal elements and an all-solid-state battery. Background Art
[0002] In recent years, with the booming development of electronic devices such as electric vehicles and drones, people's requirements for batteries have become increasingly stringent. Traditional liquid electrolyte lithium-ion batteries have many limitations. At the same time, all-solid-state lithium-ion batteries have the potential to break through the bottleneck of electrochemical energy storage and meet future development needs due to their advantages such as high safety and high energy density, attracting people's attention.
[0003] Among them, halide solid electrolytes have high oxidation stability and do not produce harmful gases after contact with air, which can further improve safety. These advantages have attracted widespread attention. However, the disadvantage of halide solid electrolytes is that their ionic conductivity is generally low, which limits the application of halide solid electrolytes. For example, in the patent with the publication number CN118173866A, a chemical formula of Li 2.3 Zr 0.6 Ce 1.7 Cl 8.2 O 0.8 The conductivity of the halide solid electrolyte is 0.71×10 -3 S cm -1 .
[0004] Therefore, the prior art still needs further improvement and development. Summary of the invention
[0005] In view of the above reasons, the purpose of the present invention is to provide a metal-nonmetallic element co-doped oxyhalide solid electrolyte and its preparation method and application. The metal-nonmetallic element co-doped oxyhalide solid electrolyte provided by the present invention can significantly improve the ion conductivity, thereby solving the technical problem that the ion conductivity of halide solid electrolytes in the prior art is generally low.
[0006] According to a first aspect of the present invention, a metal-nonmetallic element co-doped oxyhalide solid electrolyte is provided, wherein the metal-nonmetallic element co-doped oxyhalide solid electrolyte has a chemical formula of X 2a Ta b M c+2d N md Y 5b+ mc O ax; wherein X is selected from one of Li, Na, K, Ca, Mg, Zn, Al, and Fe; M is selected from one or more of Cs, Nb, Hf, La, Y, Fe, Ga, In, Pb, Bi, Ge, and Sb; N is selected from one or more of S, Se, and Te; Y is selected from one of F, Cl, Br, and I; the value ranges of a, b, c, and d are: 0 < a ≤ 4, 0 < b ≤ 2, 0 < c ≤ 2, 0 < d ≤ 2; x and m are the numerical values of the valence of element X and element M respectively.
[0007] Preferably, the metal and non-metal co-doped oxyhalide solid electrolyte is in powder form.
[0008] Preferably, the particle size of the metal and non-metal co-doped oxyhalide solid electrolyte is 1 nm - 100 μm.
[0009] According to another aspect of the present invention, there is provided a method for preparing the metal and non-metal co-doped oxyhalide solid electrolyte. Under a protective gas atmosphere, the precursors X2O x , TaY5, MY m , M2N m are mixed and ground in a molar ratio of a:b:c:d, and then ball-milled to obtain the metal and non-metal co-doped oxyhalide solid electrolyte; wherein X is selected from one of Li, Na, K, Ca, Mg, Zn, Al, and Fe; M is selected from one or more of Cs, Nb, Hf, La, Y, Fe, Ga, In, Pb, Bi, Ge, and Sb; N is selected from one or more of S, Se, and Te; Y is selected from one of F, Cl, Br, and I; x and m are the numerical values of the valence of element X and element M respectively.
[0010] Preferably, the mass ratio of the balls to the materials in the ball-milling is 5:1 - 200:1.
[0011] Preferably, the rotation speed of the ball-milling is 100 - 2000 rpm, and the time of the ball-milling is 1 h - 48 h.
[0012] According to another aspect of the present invention, there is provided an application of the metal and non-metal co-doped oxyhalide solid electrolyte in an all-solid-state battery.
[0013] According to another aspect of the present invention, there is provided an all-solid-state battery, including a solid electrolyte layer, and the solid electrolyte layer includes the metal and non-metal co-doped oxyhalide solid electrolyte.
[0014] Generally speaking, compared with the prior art by the above technical solutions conceived by the present invention, the main technical advantages are as follows:
[0015] (1) The present invention provides a metal-nonmetallic element co-doped oxyhalide solid electrolyte and its preparation method and application. The ionic conductivity of conventional halide solid electrolytes is about 1×10 -3 S cm -1 The present invention provides a halide oxide solid electrolyte with high ionic conductivity by doping metals such as Cs, Nb, Hf, La, Y, Fe, Ga, In, Pb, Bi, Ge, Sb and non-metallic elements such as S, Se, Te, and O. The room temperature ionic conductivity can reach 10×10 -3 S cm -1 The above can theoretically be applied to manufacture secondary batteries with high safety performance and high specific energy.
[0016] (2) In the present invention, preferably, the X element is Li, and lithium ions have a smaller ion radius and a stronger electric field effect in the solid electrolyte, which enables lithium ions to pass through the lattice structure more effectively, thereby having a higher mobility.
[0017] (3) The present invention provides a method for preparing a halogen oxide solid electrolyte co-doped with metal and non-metal elements. The method only requires simple ball milling, and the obtained powdered halogen oxide solid electrolyte co-doped with metal and non-metal elements can be directly used without further heat treatment. The process is simple, and the characteristics of high efficiency and low energy consumption are conducive to actual production applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The Li8Ta2Hf3Te4Cl prepared in Example 1 is 14 XRD pattern of O4.
[0019] Figure 2 The Li8Ta2Hf3Te4Cl prepared in Example 1 is 14 Electrochemical impedance spectroscopy of O4.
[0020] Figure 3 Li8Ta2Bi4S3Cl prepared in Example 3 of the present invention 16 Electrochemical impedance spectroscopy of O4.
[0021] Figure 4 The present invention is based on Li8Ta2Hf3Te4Cl in Example 1 14 The first charge-discharge cycle voltage curve of the all-solid-state battery prepared with O4 solid electrolyte.
[0022] Figure 5 Li8Ta2Bi4S3Cl prepared in Example 3 of the present invention 16 Electronic impedance spectrum of O4. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0024] Example 1
[0025] This embodiment provides a metal and non-metal element co-doped oxyhalide solid electrolyte Li8Ta2Hf3Te4Cl 14 O4, the specific preparation method is as follows:
[0026] In an Ar atmosphere glove box, weigh Li2O, TaCl5, HfCl in a molar ratio of 4:2:1:2. 4、 The HfTe2 precursor powder was placed in an agate mortar; the agate pestle was used for hand grinding for 20 minutes, and the ground precursor powder was added to a zirconia ball mill, where the ball-to-material mass ratio in the ball mill was 80:1; the ball mill was transferred to a ball mill, and the ball mill was milled at 800 rpm for 48 hours, and then the powder was cooled to room temperature naturally to prepare Li8Ta2Hf5Te4Cl 14 O4 oxyhalide solid electrolyte. The ionic conductivity of this electrolyte is 11×10 -3 S cm -1 .
[0027] Example 2
[0028] This embodiment provides a metal and non-metal element co-doped oxyhalide solid electrolyte Zn4TaLa6S6Cl 11 O4, the specific preparation method is as follows:
[0029] In an Ar atmosphere glove box, ZnO, TaCl5, LaCl3, and La2S3 precursor powders were weighed in a molar ratio of 4:1:2:2 and placed in an agate mortar; the agate pestle was used for hand grinding for 20 minutes, and the ground precursor powder was added to a zirconia ball milling jar, where the ball-to-material mass ratio in the ball milling jar was 200:1; the ball milling jar was transferred to a ball mill, and after ball milling at 800 rpm for 48 hours, it was allowed to cool naturally to room temperature to prepare powdered Zn4TaLa6S6Cl 11 O4 oxyhalide solid electrolyte. The ionic conductivity of this electrolyte is 1.6×10 -3 S cm -1 .
[0030] Example 3
[0031] This embodiment provides a metal and non-metal element co-doped oxyhalide solid electrolyte Li8Ta2Bi4S3Cl 16 O4, the specific preparation method is as follows:
[0032] In an Ar atmosphere glove box, weigh Li2O, TaCl5, and BiCl in a molar ratio of 4:2:2:1. 3、 Bi2S3 precursor powder was placed in an agate mortar; the agate pestle was used for hand grinding for 20 minutes, and the ground precursor powder was added to a zirconia ball mill, where the ball-to-material mass ratio in the ball mill was 80:1; the ball mill was transferred to a ball mill, and the ball mill was milled at 800 rpm for 48 hours, and then the ball mill was cooled naturally to room temperature to obtain powdered Li8Ta2Bi4S3Cl 16 O4 oxyhalide solid electrolyte. The ionic conductivity of this electrolyte is 7.42×10 -3 S cm -1 .
[0033] Example 4
[0034] This embodiment provides a metal and non-metal element co-doped oxyhalide solid electrolyte Na4TaGa3Te3Cl8O2, and the specific preparation method is as follows:
[0035] In an Ar atmosphere glove box, weigh Na2O, TaCl5, GaCl3, and Ga2Te3 precursor powders in a molar ratio of 2:1:1:1 and place them in an agate mortar; use an agate pestle to hand grind for 20 minutes, add the ground precursor powder into a zirconia ball mill, and the ball-to-material mass ratio in the ball mill is 100:1; transfer the ball mill to a ball mill, ball mill at 900 rpm for 48 hours, and wait for it to cool naturally to room temperature to prepare a powdered Na4TaGa3Te3Cl8O2 oxyhalide solid electrolyte. The ionic conductivity of the electrolyte is 2.56×10 -3 S cm -1 .
[0036] Example 5
[0037] This embodiment provides a metal and non-metal element co-doped oxyhalide solid electrolyte Al6TaNb2S2Br4Cl5O9, and the specific preparation method is as follows:
[0038] Al2O3, TaCl5, NbBr4, and NbSe2 precursor powders were weighed in a molar ratio of 3:1:1:1 in an Ar atmosphere glove box and placed in an agate mortar; the agate pestle was used to hand grind for 20 minutes, and the ground precursor powder was added to a zirconia ball mill, where the ball-to-material mass ratio in the ball mill was 100:1; the ball mill was transferred to a ball mill, and the ball mill was milled at 900 rpm for 48 hours, and then cooled naturally to room temperature to prepare a powdered Al6TaNb2S2Br4Cl5O9 oxyhalide solid electrolyte. The ionic conductivity of the electrolyte is 1.26×10 -3 S cm -1 .
[0039] Example 6
[0040] This embodiment provides a metal and non-metal element co-doped oxyhalide solid electrolyte Na 3.2 Ta 0.8 Ge 0.2 S 0.2 Cl 4.4 O 1.6 , the specific preparation method is as follows:
[0041] In an Ar atmosphere glove box, Na2O, TaCl5, GeCl4, and GeS2 precursor powders were weighed in a molar ratio of 1.6:0.8:0.1:0.1 and placed in an agate mortar; the agate pestle was used for hand grinding for 20 min, and the ground precursor powder was added to a zirconia ball mill, where the ball-to-material mass ratio in the ball mill was 100:1; the ball mill was transferred to a ball mill, and the ball mill was milled at 900 rpm for 48 h, and then cooled naturally to room temperature to prepare powdered Na 3.2 Ta 0.8 Ge 0.2 S 0.2 Cl 4.4 O 1.6 Oxyhalide solid electrolyte. The ionic conductivity of this electrolyte is 2.54×10 -3 S cm -1 .
[0042] Example 7
[0043] This embodiment provides a metal and non-metal element co-doped oxyhalide solid electrolyte Fe 1.6 Ta 0.8 Y 0.3 S 0.3 I 0.3 Cl4O 1.6 , the specific preparation method is as follows:
[0044] In an Ar atmosphere glove box, FeO, TaCl5, YI3, and Y2S3 precursor powders were weighed in a molar ratio of 1.6:0.8:0.1:0.1 and placed in an agate mortar; the agate pestle was used for hand grinding for 20 min, and the ground precursor powder was added to a zirconia ball mill jar, where the ball-to-material mass ratio in the ball mill jar was 120:1; the ball mill jar was transferred to a ball mill, and after ball milling at 1000 rpm for 48 h, it was allowed to cool naturally to room temperature to prepare powdered Fe 1.6 Ta 0.8 Y 0.3 S 0.3 I 0.3 Cl4O 1.6 Halogen oxide solid electrolyte. The ionic conductivity of this electrolyte is 1.08×10 -3 S cm -1 .
[0045] Example 8
[0046] This embodiment provides a metal and non-metal element co-doped oxyhalide solid electrolyte Mg 3.2 Ta 0.8 In 0.3 Te 0.3 F 0.3 Cl4O 3.2 , the specific preparation method is as follows:
[0047] In an Ar atmosphere glove box, MgO, TaCl5, InF3, and In2Te3 precursor powders were weighed in a molar ratio of 3.2:0.8:0.1:0.1 and placed in an agate mortar; the agate pestle was used for hand grinding for 20 min, and the ground precursor powder was added to a zirconia ball milling jar, where the ball-to-material mass ratio in the ball milling jar was 120:1; the ball milling jar was transferred to a ball mill, and after ball milling at 1000 rpm for 36 h, it was allowed to cool naturally to room temperature to prepare powdered Mg 3.2 Ta 0.8 In 0.3 Te 0.3 F 0.3 Cl4O 3.2 Oxyhalide solid electrolyte. The ionic conductivity of this electrolyte is 1.49×10 -3 S cm -1 .
[0048] Example 9
[0049] This embodiment provides a metal and non-metal element co-doped oxyhalide solid electrolyte K 1.6 Ta 0.8 Pb 0.2 Se 0.1 Cl 4.2O 1.6 , the specific preparation method is as follows:
[0050] In an Ar atmosphere glove box, KOH, TaCl5, PbCl2, and PbSe precursor powders were weighed in a molar ratio of 1.6:0.8:0.1:0.1 and placed in an agate mortar; the agate pestle was used for hand grinding for 20 minutes, and the ground precursor powder was added to a zirconia ball milling jar, where the ball-to-material mass ratio in the ball milling jar was 100:1; the ball milling jar was transferred to a ball mill, and after ball milling at 900 rpm for 48 hours, it was allowed to cool naturally to room temperature to prepare powdered K 1.6 Ta 0.8 Pb 0.2 Se 0.1 Cl 4.2 O 1.6 Oxyhalide solid electrolyte. The ionic conductivity of this electrolyte is 1.69×10 -3 S cm -1 .
[0051] Example 10
[0052] This embodiment provides a metal and non-metal element co-doped oxyhalide solid electrolyte Ca4Ta2Sb 0.75 Te 0.75 Cl 10 O4, the specific preparation method is as follows:
[0053] In an Ar atmosphere glove box, CaO, TaCl5, SbCl3, and Sb2Te3 precursor powders were weighed in a molar ratio of 4:2:0.25:0.25 and placed in an agate mortar; the agate pestle was used to hand grind for 20 minutes, and the ground precursor powder was added to a zirconia ball mill, where the ball-to-material mass ratio in the ball mill was 160:1; the ball mill was transferred to a ball mill, and after ball milling at 900 rpm for 48 hours, it was allowed to cool naturally to room temperature to prepare powdered Ca4Ta2Sb 0.75 Te 0.75 Cl 10 O4 oxyhalide solid electrolyte. The ionic conductivity of this electrolyte is 1.04×10 -3 S cm -1 .
[0054] Embodiment 11
[0055] This embodiment provides a metal and non-metal element co-doped oxyhalide solid electrolyte Li 6.4 Ta 0.8 Cs 0.3 S 0.1 Cl 4.1 O 3.2, the specific preparation method is as follows:
[0056] Li2O, TaCl5, CsCl, and Cs2S precursor powders were weighed in a molar ratio of 3.2:0.8:0.1:0.1 in an Ar atmosphere glove box and placed in an agate mortar. The ground precursor powders were hand-milled for 20 min using an agate pestle. The ground precursor powders were added to a zirconia ball mill with a ball-to-material mass ratio of 120:1. The ball mill was transferred to a ball mill and milled at 1000 rpm for 36 h. The powder was then cooled to room temperature to obtain powdered Li 6.4 Ta 0.8 Cs 0.3 S 0.1 Cl 4.1 O 3.2 Oxyhalide solid electrolyte. The ionic conductivity of this electrolyte is 6.49×10 -3 S cm -1 .
[0057] Example 12
[0058] This embodiment provides a metal and non-metal element co-doped oxyhalide solid electrolyte Li 3.2 Ta 0.8 Fe 0.3 S 0.3 Cl 4.3 O 1.6 , the specific preparation method is as follows:
[0059] Li2O, TaCl5, FeCl3, and Fe2S3 precursor powders were weighed in a molar ratio of 1.6:0.8:0.1:0.1 in an Ar atmosphere glove box and placed in an agate mortar; the agate pestle was used for hand grinding for 20 min, and the ground precursor powders were added to a zirconia ball mill, where the ball-to-material mass ratio in the ball mill was 100:1; the ball mill was transferred to a ball mill, and after ball milling at 900 rpm for 48 h, it was allowed to cool naturally to room temperature to prepare powdered Li 3.2 Ta 0.8 Fe 0.3 S 0.3 Cl 4.3 O 1.6 Oxyhalide solid electrolyte. The ionic conductivity of this electrolyte is 6.54×10 -3 S cm -1 .
[0060] Performance Testing
[0061] like Figure 1 As shown, the sample Li8Ta2Hf3Te4Cl obtained in Example 1 14The XRD data of O4 show that the main body of the material is amorphous.
[0062] like Figure 2 As shown, the sample Li8Ta2Hf3Te4Cl obtained in Example 1 14 The ionic conductivity of O4 can reach 11×10 -3 S cm -1 .
[0063] like Figure 3 As shown, the sample Li8Ta2Bi4S3Cl obtained in Example 3 16 The ionic conductivity of O4 can reach 7.42×10 -3 Scm -1 .
[0064] like Figure 4 As shown, the Li8Ta2Hf3Te4Cl obtained in Example 1 is used 14 O4 electrolyte assembled full battery. 0.8 Co 0.1 Mn 0.1 O2 positive electrode; Li8TaHfCl9O4 and Li6PS5Cl as electrolytes; Li-In alloy as negative electrode, charge and discharge tests were carried out at a rate of 0.2C. The full battery exhibits a high specific capacity, which is due to the fact that the Li8TaHfCl9O4 electrolyte synthesized by the synthesis method mentioned in the present invention exhibits an amorphous phase. The disordered long-range structure has a large amount of free volume, which provides a transmission channel for Li+ diffusion; and the ion transport is not hindered by the grain boundary. This ensures the internal ion transport of the battery and exhibits a high specific capacity.
[0065] like Figure 5 As shown, the sample Li8Ta2Bi4S3Cl obtained in Example 3 16 The electronic conductivity of O4 is very low, indicating that it is a good ionic conductor.
[0066] Table 1 Summary of test results
[0067]
[0068]
[0069] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A metal and non-metal element co-doped oxyhalide solid electrolyte, characterized in that: The chemical general formula of the metal and non-metal element co-doped oxyhalide solid electrolyte is X 2a Ta b M c+2d N md Y 5b+mc O ax ; where X is selected from one of Li, Na, K, Ca, Mg, Zn, Al, Fe; M is selected from one or more of Cs, Nb, Hf, La, Y, Fe, Ga, In, Pb, Bi, Ge, Sb; N is selected from one or more of S, Se, Te; Y is selected from one of F, Cl, Br, I; the value ranges of a, b, c, d are: 0 < a ≤ 4, 0 < b ≤ 2, 0 < c ≤ 2, 0 < d ≤ 2; x and m are the numerical values of the valence of element X and element M respectively.
2. The metal and non-metal element co-doped oxyhalide solid electrolyte according to claim 1, characterized in that: The metal and non-metal element co-doped oxyhalide solid electrolyte is in powder form.
3. The metal and non-metal element co-doped oxyhalide solid electrolyte according to claim 1, characterized in that: The particle size of the oxyhalide solid electrolyte co-doped with metal and non-metal elements is 1 nm-100 μm.
4. A method for preparing a metal-nonmetallic element co-doped oxyhalide solid electrolyte as claimed in any one of claims 1 to 3, characterized in that: In a protective gas atmosphere, the precursor X2O x 、TaY5、MY m 、M2N m After mixed grinding according to the molar ratio of a:b:c:d, ball milling is performed to obtain the metal and non-metal element co-doped oxyhalide solid electrolyte; wherein X is selected from one of Li, Na, K, Ca, Mg, Zn, Al, and Fe; M is selected from one or more of Cs, Nb, Hf, La, Y, Fe, Ga, In, Pb, Bi, Ge, and Sb; N is selected from one or more of S, Se, and Te; Y is selected from one or more of F, Cl, Br, and I; and x and m are the valence values of the X element and the M element, respectively.
5. The preparation method according to claim 4, characterized in that: The ball-to-material mass ratio of the ball mill is 5:1-200:
1.
6. The preparation method according to claim 4, characterized in that: The rotation speed of the ball mill is 100-2000 rpm, and the time of the ball mill is 1h-48h.
7. Use of the metal-nonmetallic element co-doped oxyhalide solid electrolyte as described in any one of claims 1 to 3 in an all-solid-state battery.
8. An all-solid-state battery comprising a solid electrolyte layer, characterized in that: The solid electrolyte layer comprises the oxyhalide solid electrolyte co-doped with a metal and a non-metal element as claimed in any one of claims 1 to 3.
Citation Information
Patent Citations
Solid electrolytic composition, electrode sheet for full-solid secondary batteries, full-solid secondary battery, and method for manufacturing electrode sheet for full-solid secondary batteries and full-solid secondary battery
CN108475817A
Solid electrolyte, solid electrolyte layer, and solid electrolyte battery
CN114207895A
Oxidation halide solid electrolyte and preparation method and application thereof
CN118748268A